(3cTa GdXdGe Yf hLhg TQGFY GdESdGes - (3eMSf Hf eQJVi Hf bGSe, J (B1238 (3g`s ((3eMeO QVG Hf eMeO GdMSfGhjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO agPG gh GdeLdO GdQGHY ef eLdOGJ cTa GdXdGe Yf hLhg TQGFY GdESdGe(B...s
(3BNQgG (B:s
(3Ef dg GdONhd Hg aj GdaQVI HfGA Ydi TQYjI YHGOJg hGdhLg Ydi dgPG GdJbOjQ(B... (3hgh BNQ GdLRA Gdhd ef GdeLdO GdQGHY(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis